Penerapan Sistem Berbasis Web untuk Meningkatkan Efektivitas Monitoring dan Evaluasi Praktek Kerja Lapangan di PT. Sanata System - Pande Nyoman Weda Wesnawa; Made Agung Raharja; I Gede Surya Rahayuda (Jurnal Pengabdian Informatika, 2026)
Effective implementation of internships requires a structured and integrated system for recording and monitoring student activities. This Community Service activity aims to implement a web-based PKL Management System at PT. Sanata System to address problems related to manual logbooks and limited monitoring by supervisors and companies. The method involved observation, interviews, socialization, and prototype system development. The system features a digital logbook, progress monitoring, and online evaluation through video calls without the need for additional installations. The implementation results indicate improved efficiency in recording activities, easier supervision by academic and field mentors, and more effective communication among stakeholders. The main finding shows that a web-based system can facilitate a more flexible, transparent, and well-documented internship monitoring and evaluation process. In conclusion, this system offers a long-term solution to enhance the quality of internship programs and is suitable for adoption by educational institutions.